2009
DOI: 10.1093/molehr/gap078
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of oxidized low-density lipoprotein and of catalase activity in follicular fluid of obese women

Abstract: The intrafollicular levels of oxidized low-density lipoprotein (oxLDL) and of enzyme antioxidants might contribute to reproductive disorders in obese and infertile women. Relevant data are missing. Eighty-four patients were grouped according to obese versus non-obese status and whether they had polycystic ovary syndrome (PCOS). The concentrations of oxLDL and the activities of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx) and glutathione reductase (GR) in the serum and follicular fluid wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 44 publications
7
54
3
Order By: Relevance
“…Some studies have consistently found increased concentration of OS markers in the follicular fluid (FF) from obese or PCOS patients when compared to controls and a relationship between increased OS level and poor outcome after in vitro fertilization has been reported [4,5]. It has been extensively reported that the effective reduction of insulin resistance obtained with metformin restores regular menstrual cycles, ovulation and improves fertility [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have consistently found increased concentration of OS markers in the follicular fluid (FF) from obese or PCOS patients when compared to controls and a relationship between increased OS level and poor outcome after in vitro fertilization has been reported [4,5]. It has been extensively reported that the effective reduction of insulin resistance obtained with metformin restores regular menstrual cycles, ovulation and improves fertility [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] In addition, it has been reported that oxidized low-density lipoprotein (LDL) which starts the atherogenesis, through foam cell formation and inflammatory responses, were found to be higher in women with PCOS than in controls. 25,26 Contrary to this process; high-density lipoprotein (HDL) shows anti-inflammatory and antioxidant effects. 27,28 Due to its small size (lower than 300 kDa); the permanent of HDL is possible to the FF.…”
Section: Discussionmentioning
confidence: 99%
“…In women who ovulate, each increase in BMI by one unit within the range of values above 29 results in a decrease in the chances for spontaneous conception by 5% [5]. However, when in the situation of application of assisted reproductive technologies in obese women, the chance for obtaining pregnancy is lower than in women with normal BM [10,11,12]. El-Toukhky et al concluded that, based on the review of 152 literature reports, obesity is related with a 3-fold increase in the risk of infertility in females, as well as the reduction of chances for successful IVF treatment [2].…”
Section: Objectivementioning
confidence: 99%